2019
DOI: 10.1002/dvdy.108
|View full text |Cite
|
Sign up to set email alerts
|

The various and shared roles of lncRNAs during development

Abstract: lncRNAs, genes transcribed but not translated, longer than 200 nucleotides, are classified as a separate class of nonprotein coding genes. Since their discovery, largely from RNAseq data, a number of pioneer studies have begun to unravel its myriad functions, centered on gene expression regulation, suggesting developmental and evolutionary conservation. Since they do not code for proteins and have no open reading frames, their functional constraints likely differ from that of protein coding genes, or of genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 82 publications
(163 reference statements)
0
21
0
Order By: Relevance
“…The long non-coding RNA (lncRNA) class includes long intergenic non-coding RNAs (lincRNAs), natural antisense transcripts (NATs), transcribed ultraconserved region (T-UCR) and non-coding pseudogenes. lncRNAs regulate stem-cell maintenance and cell differentiation, embryogenesis, X-chromosome inactivation, imprinting and the establishment of epigenetic marks [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The long non-coding RNA (lncRNA) class includes long intergenic non-coding RNAs (lincRNAs), natural antisense transcripts (NATs), transcribed ultraconserved region (T-UCR) and non-coding pseudogenes. lncRNAs regulate stem-cell maintenance and cell differentiation, embryogenesis, X-chromosome inactivation, imprinting and the establishment of epigenetic marks [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mechanism, although lncRNAs lack the capacity to encode proteins, they are able to regulate gene expression through direct or indirect mechanism 37 . Previous studies have demonstrated that lncRNA regulates target gene expression by acting as a molecular sponge for miRNA through the ceRNA pattern in the progression of ESCC 38–40 .…”
Section: Discussionmentioning
confidence: 99%
“…They present high sequence divergence between species. Nonetheless, similar or equivalent lncRNAs perform the same functions in different organisms [26]. The W chromosome is necessary for the appearance of the ovary.…”
Section: W Chromosome and Its Rolementioning
confidence: 99%